Treatment of Traumatised Sexuality - Almås, Elsa; Benestad, Esben Esther Pirelli (Frontiers in Psychology, 2021)
In light of the skills developed through therapeutic meetings with individuals who have experienced sexual violence and abuse, new challenges are emerging: How do we help these couples establish sexual relationships on their own terms, without interference of defense- or coping strategies that have been used to protect oneself against overwhelming experiences of violence or abuse in the past? This article will focus on therapeutic work with such couples and how to interact with them in their efforts to establish satisfying sexual relationships based on sexological experience as well as experience from work with traumatisation. The basis for our treatment is William Masters and Virginia Johnson´s approach. The technique of sensate focus is central, modified by trauma theory, including the understanding of dissociation, and the need to integrate memories from different levels, somatic, emotional and cognitive. The traumatised client needs special attention to experiences of predictability and safety and respect because of a history of transgression. The therapists must be aware of dissociation; different inner, dissociated parts can play different roles in the interaction between client and therapist. While couple´s therapy is a necessary frame for therapy, the therapist often needs to work with issues unique to each individual. Each partner must be able to identify their own responses and own sexual needs and preferences. It may therefore be valuable to have a co-therapist. The central goal is for the clients to identify responses to stimulation as a here and now experience in a setting that feels safe and welcome.